Application of cognitive interview in cultural adjustment of the Hidden Curriculum Evaluation Scale in Nursing Education - LI Jiyue; LIU Xiaoqin; WU Xiaxin; FAN Yaru; SHI Yuexian (Yixue xinzhi zazhi)
Objective To use cognitive interviews to explore the cognitive and conceptual understanding of the Hidden Curriculum Evaluation Scale in Nursing Education (HCES-N) among the target population in the Chinese context, and to verify the consistency between the Chinese version of HCES-N and the original scale language expression.Methods Purposive sampling method was used to recruit 14 undergraduate nursing students as interviewees from a nursing college of a university in Beijing from November 2022 to February 2023. A total of two rounds of cognitive interviews were conducted to understand the respondents' understanding of the entries in the Chinese version of the HCES-N scale, and based on the results of the interviews, the relevant entries were modified to form the Chinese version of the HCES-N. Using convenience sampling, 1,016 full-time nursing undergraduate students from 10 universities across 7 cities were recruited to conduct a validity and reliability test of the Chinese version of the HCES-N.Results The results of the first round of interviews showed that some interviewees had ambiguity in understanding 10 of the items, and had questions about the semantic expression of some items. After discussion with the research team, targeted changes were made to the relevant entries. The results of the second round of interviews showed that after consultation with experts and interviewees, the interviewees could understand contents of the revised items and the semantics were consistent with the original scale. The results of the validity and reliability analysis showed that for the Chinese version of the HCES-N, the χ2/df=6.59, RMSEA=0.074, SRMR=0.040, CFI=0.911, and TLI=0.905 and it had good internal consistency (Cronbach's α=0.945).Conclusion The use of cognitive interviews can adjust the content of the scale in a specific cultural context, optimize the scale from the perspective of the target population, ensure the understanding of the scale content by the target population, and improve the cultural adaptation effect and response quality of the scale. The Chinses version of the HCES-N adjusted using cognitive interview has good reliability and validity, and can be used to evaluate the hidden curriculum in nursing education in China.